A Theory of Cash Flow-Based Financing with Distress Resolution - Hartman-Glaser, Barney; Mayer, Simon; Milbradt, Konstantin (Review of Economic Studies, 2025)
Abstract We develop a dynamic contracting theory of asset- and cash flow-based financing that demonstrates how firm, intermediary, and capital market characteristics jointly shape firms’ financing constraints. A firm with imperfect access to equity financing covers financing needs through costly sources: an intermediary and retained cash. The firm’s financing capacity is endogenously determined by either the liquidation value of assets (asset-based) or the intermediary’s going-concern valuation of the firm’s cash flows (cash flow-based). The optimal contract is implemented with defaultable debt—specifically unsecured credit lines and senior-secured debt—and features risk-sharing via bankruptcy. When the firm does well, it repays its debt in full. When it does poorly, distress resolution mirrors U.S. bankruptcy procedures (Chapters 7 and 11). Secured and unsecured debt are complements because risk-sharing via unsecured debt increases secured debt capacity. Debt and equity are dynamic complements because future access to equity financing increases current debt capacity.